2018
DOI: 10.1016/j.repc.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cardiac resynchronization therapy on inflammatory biomarkers and cardiac remodeling: The paradox of functional and echocardiographic response

Abstract: An increase in exercise capacity after CRT implantation is associated with improvement in myocardial remodeling and inflammatory biomarkers. This finding highlights the importance of improvement in functional capacity after CRT implantation, not commonly considered a criterion of CRT response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…A close association of cytokine levels with the severity of clinical manifestations of CHF has been revealed [17]. The association of the effectiveness of CRT with a decrease in immune activation has been established [9], which is confirmed by the results of our study -a significant decrease in IL-1β, IL-6, IL-10, TNF-α was detected in the group of responders. We did not reveal any significant dynamics of CRP in the studied groups.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A close association of cytokine levels with the severity of clinical manifestations of CHF has been revealed [17]. The association of the effectiveness of CRT with a decrease in immune activation has been established [9], which is confirmed by the results of our study -a significant decrease in IL-1β, IL-6, IL-10, TNF-α was detected in the group of responders. We did not reveal any significant dynamics of CRP in the studied groups.…”
Section: Discussionsupporting
confidence: 85%
“…The molecular mechanisms of CRT influence are being actively studied. The association of cardiac remodeling in connection with CRT with a decrease in the activity of immune inflammation, neurohumoral activation, and fibrosis has been established [9][10][11]. However, none of the studied biomarkers can predict a positive response to CRT.…”
mentioning
confidence: 99%
“…Hoogslag et al investigated the agreement between these different criteria, and found that NT-proBNP reduction was more frequently correlated with echocardiographic improvement, but not with clinical response [11]. By contrast, another prospective study showed no significant BNP reduction in the group of patients with echocardiographic response [12]. However, there was a significant association between functional response determined by cardiopulmonary exercise tests and BNP reduction [12].…”
Section: Markers Of Myocyte Stressmentioning
confidence: 99%
“…Cardiac resynchronization therapy (CRT) is an effective treatment for patients with severe CHF. Based on biventricular pacing, CRT restores the electromechanical desynchrony of the heart, improving LV systolic function and reducing patient symptoms, re-hospitalizations and mortality [ 4 , 17 , 18 ]. Limited evidence suggests that CRT can reduce inflammatory mediators in HF patients [ 19 ], but the association between CRT response, T cells and cardiac remodeling in CHF is far from being understood [ 4 ].…”
Section: Introductionmentioning
confidence: 99%